Assessment of sustainability of different renewable energy systems based on life cycle exergy analysis - Petrović Branislav N. (Savez inženjera i tehničara Srbije, 2021)
The sustainable development of energy systems does not only involve the use of renewable energy resources but the increase in their efficiency as well, enabling society to maximise the benefits of their consumption. The production of electrical energy from clean and renewable sources contributes to lowered fossil fuel exploitation and the reduction of its damaging effect on the environment. This is a way to reach the global target of sustainable development - striking a balance between resource consumption and the achievable natural cycle regeneration. Environmental protection is in the focus of attention. Namely, when energy system sustainability is assessed, in addition to the ecological sustainability assessment (based on life cycle analysis - LCA), attention should be paid to the decrease in energy quality in energy processes (exergy loss). This paper presents the thermodynamic approach to energy system sustainability assessment by applying life cycle exergy analysis (LCEA). The key issue is the assessment of systems which use sustainable energy sources: the wind turbine and the stand-alone photovoltaic solar system.